Edukasi 'Sadar Anemia': Peningkatan Kesadaran Remaja Man Batubara Tentang Pentingnya Deteksi Dini Gejala Anemia Dan Penerapan Pola Makan Kaya Zat Besi - Izmi Arisa Putri Lubis; Athira Demitri; Winda Sauci Br Panjaitan; Vania Amanda; Dhea Syafitri; Putri Rahmi Virani Lubis (STIKES Columbia Asia Medan, 2025)
Iron Deficiency Anemia is a common health problem among adolescents, particularly females, and is associated with decreased concentration, fatigue, and reduced academic performance. This community service program aimed to increase students’ awareness and knowledge regarding early detection of anemia symptoms (5L) and the adoption of iron-rich dietary practices. The intervention was conducted through interactive health education sessions involving lectures, discussions, and questions and answers with 30 students of MAN Batubara. The results indicated an improvement in students’ understanding of anemia symptoms, early behavioral changes in choosing iron-rich foods, and the emergence of local student leaders who supported peer awareness. This participatory educational approach proved effective in enhancing nutritional literacy and collective awareness toward anemia prevention among adolescent